+0  
 
0
281
2
avatar

$${\frac{{{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}}{{{log}}_{{\mathtt{2}}}{\left({\mathtt{4\,096}}\right)}}} = -{\mathtt{4}}$$

Guest Mar 14, 2015

Best Answer 

 #1
avatar
+10

$${\frac{{{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}}{{{log}}_{{\mathtt{2}}}{\left({\mathtt{4\,096}}\right)}}} = -{\mathtt{4}}$$

 

$${{log}}_{{\mathtt{2}}}{\left({\mathtt{4\,096}}\right)} = {\mathtt{12}}$$

 

$${\frac{{{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}}{{\mathtt{12}}}} = -{\mathtt{4}}$$

 

$${{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)} = -{\mathtt{48}}$$

 

$${{\mathtt{x}}}^{-{\mathtt{48}}} = {\frac{{\mathtt{37}}}{{\mathtt{999}}}}$$

 

$${\frac{{\mathtt{1}}}{{{\mathtt{x}}}^{{\mathtt{48}}}}} = {\frac{{\mathtt{37}}}{{\mathtt{999}}}}$$

 

$${\mathtt{999}} = {\mathtt{37}}{\mathtt{\,\times\,}}{{\mathtt{x}}}^{{\mathtt{48}}}$$

 

$${\mathtt{27}} = {{\mathtt{x}}}^{{\mathtt{48}}}$$

 

$${\sqrt[{{\mathtt{{\mathtt{48}}}}}]{{\mathtt{27}}}} = {\mathtt{x}}$$

 

$${\sqrt[{{\mathtt{{\mathtt{48}}}}}]{{\mathtt{3}}{\mathtt{\,\times\,}}{\mathtt{3}}{\mathtt{\,\times\,}}{\mathtt{3}}}} = {\mathtt{x}}$$

 

$${\mathtt{x}} = {\sqrt[{{\mathtt{{\mathtt{16}}}}}]{{\mathtt{3}}}}$$

Guest Mar 14, 2015
 #1
avatar
+10
Best Answer

$${\frac{{{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}}{{{log}}_{{\mathtt{2}}}{\left({\mathtt{4\,096}}\right)}}} = -{\mathtt{4}}$$

 

$${{log}}_{{\mathtt{2}}}{\left({\mathtt{4\,096}}\right)} = {\mathtt{12}}$$

 

$${\frac{{{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}}{{\mathtt{12}}}} = -{\mathtt{4}}$$

 

$${{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)} = -{\mathtt{48}}$$

 

$${{\mathtt{x}}}^{-{\mathtt{48}}} = {\frac{{\mathtt{37}}}{{\mathtt{999}}}}$$

 

$${\frac{{\mathtt{1}}}{{{\mathtt{x}}}^{{\mathtt{48}}}}} = {\frac{{\mathtt{37}}}{{\mathtt{999}}}}$$

 

$${\mathtt{999}} = {\mathtt{37}}{\mathtt{\,\times\,}}{{\mathtt{x}}}^{{\mathtt{48}}}$$

 

$${\mathtt{27}} = {{\mathtt{x}}}^{{\mathtt{48}}}$$

 

$${\sqrt[{{\mathtt{{\mathtt{48}}}}}]{{\mathtt{27}}}} = {\mathtt{x}}$$

 

$${\sqrt[{{\mathtt{{\mathtt{48}}}}}]{{\mathtt{3}}{\mathtt{\,\times\,}}{\mathtt{3}}{\mathtt{\,\times\,}}{\mathtt{3}}}} = {\mathtt{x}}$$

 

$${\mathtt{x}} = {\sqrt[{{\mathtt{{\mathtt{16}}}}}]{{\mathtt{3}}}}$$

Guest Mar 14, 2015
 #2
avatar+92781 
0

Excellent answer anon :)

Melody  Mar 14, 2015

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.